Learning Strategies For Children Special Needs: Strategi Pembelajaran Untuk Anak Berkebutuhan Khusus - Prawesti, Anisa Julia; Anuraga, Bayu Septian; Nugraha, Rio Setya Budi (Proceedings of The ICECRS, 2020)
This study aims to determine the Learning Strategies For Children Special Needs. The method used in this research is the study of literature. This research produces educational services for individuals with special needs is inclusive education by deepening the application of learning strategies for children with special needs.